2022
DOI: 10.3329/bjms.v21i3.59574
|View full text |Cite
|
Sign up to set email alerts
|

Video-based versus educational booklet training on self-care performance of patients with cataract

Abstract: Background and Objective: Training patients can increase their knowledge and skills in self-care performance after cataract surgery. The present study compared the effect of videobased training and educational booklet methods on the self-care performance of patients with cataracts. Methods and Material: In this interventional study,83eligible patients a day prior to their cataract surgery were enrolledin the study based on the convenient sampling method conducted in 2020.Then, the patients were allocated into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(23 reference statements)
0
0
0
Order By: Relevance
“…Studies have shown that self-care with the help of educational videos can be used for individuals with different health conditions. A study conducted in Iran showed that video training had a positive effect on self-care in cataract patients (26). A study conducted in India indicated that video training can improve self-care in patients with epilepsy (27).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that self-care with the help of educational videos can be used for individuals with different health conditions. A study conducted in Iran showed that video training had a positive effect on self-care in cataract patients (26). A study conducted in India indicated that video training can improve self-care in patients with epilepsy (27).…”
Section: Discussionmentioning
confidence: 99%